IMPACT OF A COVID-19 PANDEMIC HANDLING POLICY IN THE EDUCATION FIELD - Fadhilah Fadhilah; Mita Widyastuti (Universitas Dharma Wacana, 2022)
Since the outbreak of the Corona virus which shocked the world, numerous countries have enacted policies to restrict its spread. The Indonesian government has undertaken several initiatives, including the introduction of Large-Scale Social Restrictions (PSBB). This policy resulted in the implementation of online learning. In case study research at UNISMA Bekasi, the evaluation of online learning results based on the experiences of researchers and data from several tenured lecturers revealed a decline in quality. This study employed a qualitative methodology with a phenomenological-participatory approach in which the researchers were also participants in online learning process. The findings show that the quality of responses to questions on the Mid-Semester Examination (UTS) and the Final Semester Examination (UAS) was deemed by some lecturers to be significantly dependent on the capacity of students to download and copy-paste from the internet. The researchers discovered some online responses to UTS and UAS questions that were irrelevant to the questions’ intended purposes. This was also observed in students whose grades for a series of theoretical courses appeared to be good and whose total GPA was satisfactory, but somehow, they had difficulties answering examiners’ questions during the oral defense of their undergraduate dissertation proposal. In conclusion, the GPA derived from online learning outputs cannot be considered as a measure of students’ theoretical mastery. The issue demands a more inventive, communicative, and collaborative online learning system to address the shortcomings of the online learning process. It is anticipated that mastery of theory will enhance students’ capacity to apply it in scientific and everyday settings.